HEALTH TOURISM IN THE UNITED STATES: CONSUMER BEHAVIOR, MARKET TRENDS, AND REGIONAL DEVELOPMENT OPPORTUNITIES - Oznobishyna, Maryna (Global Prosperity, 2026)
Wellness tourism in the United States has grown into a $120 billion market, reflecting a broader global industry worth nearly $900 billion. At the same time, Americans are reporting record levels of stress: according to Gallup, almost half of adults experience it daily, and the American Psychological Association has described the current climate as one of "collective trauma." Consequently, the observed growth in wellness tourism may be attributed to a heightened consumer demand for destinations and experiences that facilitate comprehensive physical and psychological restoration. This article analyzes the motivational structure of demand, consumer segmentation, service formats, and regional market differentiation, as well as the operational determinants of client satisfaction with wellness programs. Methods of analyzing and systematizing secondary data were applied, based on materials from the Global Wellness Institute (2023–2025), the American Psychological Association, Gallup, and industry analytical organizations, as well as comparative operational data from three tourism companies for the years 2017–2021. Five demand factors were identified, with the inability of habitual stress-coping mechanisms to ensure recovery being the leading one. Four consumer segments with distinct demands, six service formats, and regional market clusters are described. The scientific novelty lies in the introduction of an operational measure of customer satisfaction into the market analysis: it was found that preparing the client for the program reduces the proportion of complaints due to unmet expectations by 57–70%. These findings are systematized in the author's original contribution: the Expectation Alignment Framework, which identifies expectation gaps as the primary complaint driver in wellness tourism, and the Operational Satisfaction Model, which links structured pre-departure preparation to measurable client outcomes.